An Empirical Study Of E-Healthcare Industry In India - Krishnamurthy, Ramkumar (2005)
This paper aims at studying the state of the online healthcare industry in India, and the current trends. The study also tries to trace the future potential of this industry by trying to find out the perspective of consumers on internet usage for healthcare services.